Ionospheric disturbances as precursor signals of the March 28, 2025, Myanmar earthquake - Pansong, C.; Ruttanaburee, S.; Pornsopin, P.; Kenpankho, P. (My University, 2026)
This study examined the ionospheric response associated with the Mw 7.7 Myanmar earthquake on March 28, 2025, using GPS-derived Total Electron Content (TEC) data from seven GNSS stations across Thailand. TEC variations were analyzed alongside Dst and Kp indices, as well as ionosonde-derived parameters, namely the critical frequency of the F2 layer (foF2), the peak height of the F2 layer (hmF2), the disturbances in NmF2, and the slab thickness (τ), which were obtained from three IGS-supported stations. We detected abnormal variations in TEC approximately 15 days before the earthquake (13–27 March 2025), characterized by alternating positive and negative deviations. The TEC exhibited alternating positive and negative deviations throughout the analysis period, reflecting ionospheric variability prior to the earthquake. During the early period (13–18 March), the deviations remained within approximately ±6 TECU. However, from 19 to 21 and 23–24 March, moderate fluctuations were observed, particularly at mid- and low-latitude stations (UTHG, THBK, THCP, and THPK), where ΔTEC ranged from ±6 to 10 TECU. The TEC decrease occurred on 25 March under weak geomagnetic conditions (Dst >  −30 nT) at the northern stations MAEH (−18.40 TECU), THCM (−15.65 TECU), and NANN (−15.73 TECU), marking the most pronounced negative anomaly observed during the study period. Subsequently, on 26–27 March, TEC values recovered to positive anomalies of +4 to +10 TECU, indicating a return to normal ionospheric conditions. To objectively identify pre-seismic ionospheric anomalies, a Median Absolute Deviation (MAD) approach was applied using a ±1.34MAD threshold. This statistical technique effectively detects subtle deviations while minimizing transient noise. The results reveal coherent TEC depletions across multiple stations on 25 March, suggesting the presence of localized ionospheric disturbances potentially related to seismo-ionospheric processes rather than geomagnetic effects. Furthermore, concurrent anomalous increases in foF2 and hmF2, along with a reduction in slab thickness near the epicentral region, indicate vertical uplift of the F2 layer, consistent with possible Lithosphere–Atmosphere–Ionosphere Coupling (LAIC) mechanisms.
Keywords: foF2; hmF2; Ionospheric disturbances; Myanmar earthquake; NmF2; TEC